Emergency Volunteer Retention: Can a Culture of Inclusiveness Help? - Gagné, Marylène; Luksyte, Aleksandra; Dunlop, Patrick; Holtrop, Djurre; Kragt, Darja; Farid, Hawa Muhammad (2019)
Given increasingly diversified communities and the importance of attracting and retaining all volunteers irrespective of their demographic background, it is important to increase the representativeness of volunteers by promoting diversity. We surveyed emergency services volunteers from Western Australia to examine (a) whether and why culture of inclusiveness plays an important role for volunteer retention and (b) whether and why female volunteers have different perceptions of inclusivity culture in their units. Our findings demonstrated that climate for inclusion played a vital role for volunteer retention because in such climates they felt connected and related to others, and felt freedom to express themselves professionally. Despite the importance of climate for inclusion, male and female volunteers viewed this climate differently and experienced different outcomes. Female volunteers perceived marginally lower levels of climate of inclusion than men. As hypothesised, female volunteers felt more connected to their teammates in inclusive climates integrative of differences. Unexpectedly, female volunteers’ relatedness needs were less likely to be fulfilled in inclusive climates where they were included into decision-making.